Coping with Learning Disability in a Dyslexic Child in Terms of an Instructional Model - Fitriani, S; Felina, S (KnE Social Sciences, 2018)
The children with dyslexia might have difficulty in reading and writing, with most normal children being able to read and write at the age of around 5 to 6 years. The movie Like Stars on Earth depicts the story of a boy named Ishaan, who suffers from dyslexia, and how his teacher assists him in terms of the learning process. This article aims to analyze and elaborate the types of instructional model applied by Mr. Nikumbh, Ishaan’s teacher, who gives a specific different treatment to him with a view to improving his reading and writing ability. Keywords: dyslexia, multisensory teaching, Orton-Gillingham approach